Development of the human pancreas and its exocrine function - Mehta, Vijay; Hopson, Puanani E.; Smadi, Yamen; Patel, Samit B.; Horvath, Karoly; Mehta, Devendra I. (Frontiers in Pediatrics, 2022)
The pancreas has both endocrine and exocrine function and plays an important role in digestion, and glucose control. Understanding development of the pancreas, grossly and microscopically, and the genetic factors regulating it provides further insight into clinical problems that arise when these processes fail. Many developmental studies have been conducted on animal models, which due to genetic differences, do not completely mirror the human development. Therefore, in this review we focus on human studies that have reported the gross and the microscopic development including acinar-, ductal-, endocrine cells and the neural network. We describe the gene expressions and transcription factors involved in the organ formation but use animal models to bridge current understanding where it is necessary. A deeper review of the genes involved in pancreatic formation allows us to describe the development of the different groups (proteases, lipids, and amylase) of enzymes during fetal life and postnatally and describe the genetic defects. We discuss the constellation of gross anatomical, as well as microscopic defects that with genetic mutations lead to pancreatic insufficiency and disease states.